(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: Health tourism is an important and growing industry in the world. Iran has long been one of the active centers of health tourism in the Middle East region. Due to the important role of the medical tourism industry in the global economy, this study aimed to determine factors affecting and challenges on medical tourism. Methods: A mixed methods (quantitative and qualitative) study was carried out in the southeast of Iran, where has a border with Afghanistan and Pakistan countries. All patients who were referred to Sistan and Baluchistan province hospitals (six hospitals) between 2010 - 2018 were selected with the census method. In the qualitative phase, a semi-structured interview had done on 17 experts specialized in health tourism in 2019. All interviews were recorded and written daily. Finally, the data were analyzed by the content analysis method. Results: About 349 health tourists had referred to the selected hospitals from 2010 to 2018, of which 213 (61%) patients were male and 234 persons (39%) were married. The majority of the patients belonged to Afghanistan (190 patients, 54.4%). Four main themes affect the development of the medical tourism industry included human resource, specialized services, facilities, and infrastructure services and security conditions. Conclusion: Despite the high capacity of health tourism in the southeast of Iran, a few health tourists used the hospital services. Planning and policy-making must be done correctly in the field of infrastructure, medical equipment, marketing, and advertising. Also, attention should be paid to transportation infrastructure for easy access to these centers, as well as training capable and specialized medical staff in various medical centers. Keywords: Evaluation, Development Barriers, Health Tourism.